2005
DOI: 10.1007/s10195-005-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Morton’s neuroma: the evidence

Abstract: Morton's neuroma is a common injury of the forefoot that affects the third web space of the toes. The pain, localized to the forefoot and toes, may appear gradually but usually becomes significant and persistent. Often it occurs after walking and is relieved by removing the shoe and manipulating the forefoot. The management of this condition varies widely and includes conservative and surgical treatments. There is no general agreement on the optimal treatment for this pathology. The aim of this review was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Currently, as many as 70% of those with PDN receive surgical intervention prior to any conservative treatment at all other than a corticosteroid injection 5 the value of which has been questioned in relation to PDN. 18,27 Rasmussen reports that 20% of patients experienced no benefit at all from a steroid injection, with a further 54% experiencing a benefit which lasted for less than three months. 27 A later study demonstrated that 41% of patients were dissatisfied with the outcome of steroid injection therapy in relation to PDN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, as many as 70% of those with PDN receive surgical intervention prior to any conservative treatment at all other than a corticosteroid injection 5 the value of which has been questioned in relation to PDN. 18,27 Rasmussen reports that 20% of patients experienced no benefit at all from a steroid injection, with a further 54% experiencing a benefit which lasted for less than three months. 27 A later study demonstrated that 41% of patients were dissatisfied with the outcome of steroid injection therapy in relation to PDN.…”
Section: Discussionmentioning
confidence: 99%
“…11,17 Despite the range of advocated interventions, there is little agreement among clinicians as to the best treatment protocol for PDN. 18 It remains a difficult condition to resolve and is often a limiting factor in the individuals leisure pursuits and work life. 5,19 There is as yet very little empirical evidence that supports the use of one therapy over another and, despite surgery being generally accepted as the gold standard treatment, there is to date no evidence that it results in better patient outcomes than conservative care.…”
Section: Introductionmentioning
confidence: 99%